Utilising a multi‐item questionnaire to assess household food security in Australia. (11th April 2018) - Butcher, Lucy M.; O'Sullivan, Therese A.; Ryan, Maria M.; Lo, Johnny; Devine, Amanda
Abstract: Issue addressed: Currently, two food sufficiency questions are utilised as a proxy measure of national food security status in Australia. These questions do not capture all dimensions of food security and have been attributed to underreporting of the problem. The purpose of this study was to investigate food security using the short form of the US Household Food Security Survey Module (HFSSM) within an Australian context; and explore the relationship between food security status and multiple socio‐demographic variables. Methods: Two online surveys were completed by 2334 Australian participants from November 2014 to February 2015. Surveys contained the short form of the HFSSM and twelve socio‐demographic questions. Cross‐tabulations chi‐square tests and a multinomial logistic regression model were employed to analyse the survey data. Results: Food security status of the respondents was classified accordingly: High or Marginal (64%, n = 1495), Low (20%, n = 460) or Very Low (16%, n = 379). Significant independent predictors of food security were age ( P < 0.001), marital status ( P = 0.005), household income ( P < 0.001) and education ( P < 0.001). Conclusion: Findings suggest food insecurity is an important issue across Australia and that certain groups, regardless of income, are particularly vulnerable. So what?: Government policy and health promotion interventions that specifically target "at risk" groups may assist to more effectively address the problem. Additionally, the use of a multi‐item measure is worth considering as a national indicator of food security in Australia.